Atividade experimental para o estudo dos fundamentos do eletromagnetismo e da corrente elétrica alternada. - Dionisio, Guilherme (2017)
The present work describes the development of an experimental apparatus for visualizing the waveform (FO) of alternating electric current in household appliances. This equipment is the result of a research in the line of Technologies of information, communication and interaction applied to the teaching of Sciences and Mathematics. It is a tool to be used by physics teachers in the teaching of electromagnetic phenomena, including alternating electric current, considering that there are few experimental teaching proposals related to this content. The use of the tool covers basic, technical and higher education. For the development of the apparatus, a toroid was used as a current sensor, the Arduino board, as an analog-to-digital converter, and computer programs for data processing and plotting. For a simple application, the microphone input of the computer and the audio program Audacity for the visualization of the FO are used. For further study, we use Arduino and its own authoring program written in the Python language integrated with a spreadsheet. In the second case, it is possible to visualize the FO, decompose the current signal into its 60 Hz harmonics and analyze these results through an Excel spreadsheet prepared to receive this data. With the intention of disseminating the work in a way that it can be used by other teachers, a booklet has been elaborated that directs step by step the physical assembly of the experiment and use of the created programs and worksheets, which are also available for download. As a suggestion foruse in basic education, the developed product presents an easy sequence centered on the production, transportation and distribution of electric energy, based on the three pedagogical moments of Delizoicov & Angotti, which leads the student to understand phenomena of electromagnetism and into the study of digital devices. For this, we use instruments such as videos, animations, computer simulators, and the experimental apparatus mentioned. The content analysis of texts and reports prepared by the students, according to the proposal of Laurence Bardin, was used to evaluate the learning of the content worked with two classes of the third year of high school and the potentialities of the use of the apparatus.